2009
DOI: 10.1039/b816827j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of water nanodroplets and aqueous protons in non-ionic reverse micelles

Abstract: We present a study of the microscopic dynamics of water trapped in reverse non-ionic micelles by means of a series of molecular dynamics simulations. The analysis of the effects of micellar confinement on spectroscopical properties of an excess proton has also been considered. Our micelles were microemulsions made with the neutral surfactant diethylene glycol monodecyl ether [CH 3 (CH 2 ) 11 (OC 2 H 4 ) 2 OH]. Simulation experiments including the proton species were performed using a multistate empirical valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It appears also that water plays a crucial role in determining the stability of the microemulsions 326,333 depending on the "type" of water molecules: bulk-like water molecules or self-associated into the reverse micelles. 324,334,337 Another parameter that should be considered is the influence of electrolytes on the lateral equation of state linking area per molecule to the free energy of the surfactant film. This is especially true in the case of ultraflexible microemulsions for which the surfactant layer is much thinner than a complete monolayer.…”
Section: F F Tsmentioning
confidence: 99%
“…It appears also that water plays a crucial role in determining the stability of the microemulsions 326,333 depending on the "type" of water molecules: bulk-like water molecules or self-associated into the reverse micelles. 324,334,337 Another parameter that should be considered is the influence of electrolytes on the lateral equation of state linking area per molecule to the free energy of the surfactant film. This is especially true in the case of ultraflexible microemulsions for which the surfactant layer is much thinner than a complete monolayer.…”
Section: F F Tsmentioning
confidence: 99%
“…While the typical model takes into consideration two states of water molecules [77], i.e., a layer located nearby the surfactant interface corresponding to the "bound" layer and the bulk-like water in the interior of the water pool considered to be the "free" form, a more complete model identified a structural heterogeneity described by three species of water molecules, with the third specie of water being the molecules "trapped" at the surfactant interface ( Figure 6) [78][79][80][81]. The region consisting of trapped water is the nearest layer to the surfactant cavity and is composed of molecules which interact directly with the large immobilized headgroups of surfactants, forming a cluster around them, while the H-bonds between water molecules do not exist.…”
Section: Water Pool Structurementioning
confidence: 99%
“…Reverse micellar (RM) systems have evolved as a potential reaction medium to carry out various chemical reactions otherwise difficult to control in homogeneous media due to highly structured water molecules present in the system. [1][2][3][4][5][6][7] In recent years, there have been a number of applications of RMs for controlled enzymatic reaction, 8,9 biomedical informatics, 10 DNA hybridization 11 and its sequence-selective extraction, 12 and size-selective preparation of nanoparticles. 13,14 It is concluded that dynamical freedom of the water molecules present in the RM is responsible for the precise control of the reactions.…”
Section: Introductionmentioning
confidence: 99%